How to Identify the Crystal Growth Unit. Issue 11 (27th October 2021) - Verma, Lakshmanji; Warzecha, Monika; Chakrabarti, Rajshree; Hadjiev, Viktor G.; Palmer, Jeremy C.; Vekilov, Peter G.
Abstract: The structure and composition of the crystal growth unit are of huge fundamental and practical consequence. We propose a method to identify the solute species that incorporates into the growth site on crystal surfaces, the kinks, which rests on the kinetics of the elementary reaction at the kinks. We use as model crystals olanzapine, an antipsychotic medication, and etioporphyrin I, a field‐effect transistor. We combine time‐resolved in situ atomic force microscopy with Raman and absorption spectroscopies, complemented by density functional theory and all‐atom molecular dynamics modeling of the solutions. We show that the structure of the growth unit cannot be deduced neither from the solute oligomers nor from the crystal structure. Chemical kinetics analyses reveal that if the dominant solute species is the one that incorporates into the crystal growth sites, then the kinetics of layer growth complies with a monomolecular rate law. By contrast, if the crystal growth unit assembles from two units of the dominant solute form, a bimolecular rate law ensues. Solutions of both olanzapine and etioporphyrin I are dominated by solute monomers, which exist in equilibrium with a minority of dimers. Whereas numerous olanzapine crystal structures incorporate dimer motifs, etioporphyrin I crystals organize as stacks of monomers. Olanzapine crystal grow by incorporation of dimers. One of the studied face of etioporphyrin I grows by incorporation of the majority monomers, whereas the other one selects the minority dimers as a growth unit. The results highlight the power of the crystallization kinetics analyses to identify the growth unit and illuminate one of the most challenging issues of crystal growth. Abstract :